2020
DOI: 10.3390/ani10060948
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamic Changes of African Elephant Milk Composition over Lactation

Abstract: The combined data of milk composition of 14 African elephants over 25 months of lactation are presented. The milk density was constant during lactation. The total protein content increased with progressing lactation, with caseins as the predominant protein fraction. The total carbohydrates steadily decreased, with the oligosaccharides becoming the major fraction. Lactose and isoglobotriose reached equal levels at mid lactation. The milk fat content increased during lactation, as did the caprylic and capric aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 65 publications
3
14
0
Order By: Relevance
“…The influence of lactation stage on EMF reported here agrees with the observations for EMF described in a recent study [ 13 ] and with the effects reported for other mammals. Earlier studies showed a significant effect of lactation stage on bovine MF composition.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The influence of lactation stage on EMF reported here agrees with the observations for EMF described in a recent study [ 13 ] and with the effects reported for other mammals. Earlier studies showed a significant effect of lactation stage on bovine MF composition.…”
Section: Discussionsupporting
confidence: 93%
“…A detailed description of the effect of lactation stage on macro‐ and micronutrients, and fat composition in specific, of elephant milk can be found elsewhere. [ 13 ] Here, we focus on the effect of substantial FA changes in EMF TAG and crystallization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increases in fat and crude protein content and decreases in sugar content found in this study (Table 3; Figure 1) are consistent with other published studies on African elephant milk (Table 2, Kobeni et al, 2020; McCullagh & Widdowson, 1970; Osthoff et al, 2005, 2007). The mean values for fat, protein and sugar from the previous zoo elephant studied during early lactation (Parrot, 1996) are consistent with the early lactation values from our study, providing further evidence that elephant milk increases in nutrient density over lactation.…”
Section: Discussionsupporting
confidence: 93%
“…The most recent published data from free‐ranging elephants in Africa (Kobeni et al, 2020) found the same consistent changes in milk composition across lactation as this study, with fat and protein increasing and sugar decreasing. Thus, both captive North American African elephants and free‐ranging elephants in Africa display the same pattern of increasing milk nutrient density over lactation, strongly suggesting that these patterns are fixed and relatively unaffected by external factors such as diet.…”
Section: Discussionsupporting
confidence: 87%